KEBERMAKNAAN HIDUP NARAPIDANA DITINJAU DARI PENDEKATAN EKSISTENSIAL - M. Hestu Widiyastana; Indah Fajrotuz Zahro (Ilmu Psikologi Universitas Yudharta Pasuruan)
AbstractThe meaning of life is a value that a person believes and becomes the basis of people's behavior in living the process of life. And become an important thing as the foundation of human existence. The meaning of life is personal and can be found in any conditions and however by every individual even being a prisoner who is languishing in a penitentiary with limitations and loss of freedom possessed. There are values that become the the source of meaningful life of the inmates as the results of this study show that from the three subjects of which two of them re-discover the meaning of life that is the creative value, value of appreciation and the value of attitude. So it can be a healthy person like the individual in general while one subject can no longer find the meaning of life it is influenced by the fulfillment or not the needs of the subject and the level of quality of appreciation, value of attitude and their different creativity.